THE SCOPE OF AYURVEDIC MEDICINE AND THERAPY IN THE MANAGMENT OF INFERTILITY (International Journal of Ayurveda and Pharma Research, 2018)
Infertility is described as an inability to conceive despite unprotective sex for duration of one year or more. Male, female or both can be a victim for this disorder. There may be many biological causes of infertility including some can be treated with medical or surgical intervention. Ayurveda consider this problem as a cause of deterioration of quality of four factors i.e., time of ovulation, female health in context of reproductive system, quality of sperm and ovum and female’s proper nutrition. There are different treatment methods and medicines used according to the deficit in male, female or in both. Vajikaran drugs like Ashwagandha, Madhuyasthi, Vidarikanda, Gokshura etc., are used in male fertility problems and Satavari, Punarnava, Dasmoola, Aloevera etc., used in female infertility problems. The purificatory procedures like Vamana, Virechana, Basti etc., are also found very effective to improve the quality and strength of required reproductive factors in both sexes. The effect of Uttar basti is also evidenced in different researches to treat female infertility.